Analisis Pengaruh Makroekonomi dan Kinerja Perusahaan Terhadap Harga Saham Syariah pada Indeks Saham Syariah Indonesia - Ega Risti Safany; Iwan Setiawan; Fifi Afiyanti Tripuspitorini (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study point is to know the influence of macroeconomic factors inclusive of inflation, exchange rates, interest rates and company performance consisting of ROA, DER, EPS on Sharia stock prices on the Indonesian Sharia Stock Index (ISSI) for the 2013-2019 period. The research methodology used is descriptive-quantitative method using multiple linear regression analysis techniques. This study uses secondary data derived from data from Bursa Efek Indonesia (BEI) and Badan Pusat Statistik (BPS). The object of this research is companies that are included in ISSI with a total sample of 108 companies that have met the sample selection criteria, namely the purposive sampling method. Hypothesis testing is done by using a path diagram. The results of this study indicate that macroeconomic factors including inflation, exchange rates, interest rates partially have no influence on Sharia stock prices. Company performance factors such as ROA and EPS have a positive impact on Sharia stock prices, while DER has no influence.